A Tet-on and Cre-loxP based genetic engineering system for convenient recycling of selection markers in Penicillium oxalicum - Baojie eJiang; Ruiqin eZhang; Dan eFeng; Fangzhong eWang; Kuimei eLiu; Yi eJiang; Kangle eNiu; Quanquan eYuan; Mingyu eWang; Hailong eWang; Hailong eWang; Youming eZhang; et al. (Frontiers in Microbiology, 2016)
The lack of selective markers has been a key problem preventing multistep genetic engineering in filamentous fungi, particularly for industrial species such as the lignocellulose degrading Penicillium oxalicum JUA10-1(formerly named as Penicillium decumbens). To resolve this problem, we constructed a genetic manipulation system taking advantage of two established genetic systems: the Cre-loxP system and Tet-on system in Penicillium oxalicum JUA10-1. This system is simple and efficient. The expression of Cre recombinase was activated by doxycycline since it was controlled by Tet-on system. Using this system, two genes, ligD and bglI, were sequentially disrupted by loxP flanked ptrA. The successful application of this procedure will provide a useful tool for genetic engineering in filamentous fungi. This system will also play an important role in improving the productivity of interesting products and minimizing by-product when fermented by filamentous fungi.